PENGUATAN KELEMBAGAAN PENGELOLA HUTAN DESA DI SEKITAR GUNUNG RAJABASA LAMPUNG - Rommy Qurniati; Duryat Duryat; Hari Kaskoyo (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2017)
Abstract Management of forest area could not be separated from the communities who are living surrounding and their depending on the forest area and its products. As a manifestation of social responsibility, Lampung University has been conducting a program of KKN-PPM in order to increase the community welfare at once keep maintaining the forest function. The activity intended to increase capacity of Forest Village Admninistrator Agency (LPHD) and village officials in terms of institutional ability administration and group dynamics. A method of lecture and discussion, followed by practice demonstration and 40 days accompaniment were employed as training method. The result showed that the training has proven to be very effective in improving the ability of participants cognitively, affectively and psychometrically in terms of administrative definition, types of administrative tools, characteristics and functions of group dynamics, communication, leadership and groups synergies, as well as factors influence the quality of relationships within a group. Therefore, the efforts to strengthened LPHD should be implemented continuously to create a dynamic group where the members were actively involved, responsible and skilled to work in the group. This training was also very effective to be a means of capacity building of the community and students. Keywords: forest village, Forest Village Admninistrator Agency, institution straighten Abstrak Pengelolaan wilayah hutan, tidak dapat dilepaskan dari masyarakat sekitar yang menggantungkan hidup dari kawasan dan hasil hutan. Sebagai wujud dari tanggungjawab sosial perguruan tinggi, Universitas Lampung dengan program KKN-PPM melaksanakan kegiatan dalam rangka meningkatkan kesejahteraan masyarakat dengan tetap menjaga kelestarian fungsi hutan. Kegiatan ini bertujuan untuk meningkatkan kapasitas pengurus LPHD dan aparat desa dalam hal kemampuan administrasi kelembagaan dan dinamika kelompok. Kegiatan ini dilaksanakan dengan metode ceramah dan diskusi, diikuti dengan demonstrasi praktek, dan kemudian pendampingan masyarakat selama 40 hari. Kegiatan ini terbukti sangat efektif untuk meningkatkan kemampuan peserta baik dari segi kognitif, afektif dan psikomorik dalam hal pengertian administrasi, jenis-jenis perangkat administrasi, ciri-ciri dan fungsi dinamika kelompok, komunikasi, kepemimipinan dan sinergi dalam kelompok, serta faktor-faktor yang mempengaruhi kualitas hubungan di dalam suatu kelompok. Oleh karena itu upaya penguatan kelembagaan LPHD perlu terus digalakkan agar terwujud lembaga yang dinamis dengan anggota yang terlibat aktif, bertanggungjawab dan terampil dalam bekerjasama. Kegiatan pelatihan ini juga sangat efektif menjadi sarana belajar bersama bagi peningkatan kapasitas masyarakat dan mahasiwa. Kata kunci: hutan desa, LPHD, penguatan kelembagaan